HUBUNGAN TINGKAT PENGETAHUAN DENGAN SIKAP BIDAN MENGENAI TEKNIK INSPEKSI VISUAL ASETAT (IVA) DALAM SKRINING KANKER SERVIKS DI PUSKESMAS KOTA PADANG - Pelsi Sulaini; Edison Edison (Universitas Andalas, 2019)
Using Visual Inspection with Acetic Acid (VIA) as one examination for cervical cancer screening not well-known among health workers in Padang. This study was conducted to know the level of knowledge and attitudes of midwives about cervical cancer screening using Visual Inspection with Acetic Acid (VIA) examination in Primary Health Center in Padang. This was a cross-sectional analytic study and has been performed in the Primary Health Center in Padang from July –August 2014. The selection of the research subjects was performed to a midwife who worked in a gynecological clinic that meets inclusion criteria. We found 48 midwives that met inclusion criteria, guided interviews were conducted with a questionnaire, data recapitulated, and computerized processed using computer software and performed statistical tests. There was a weak correlation between the level of knowledge (X) and attitude (Y) about Visual Inspection with Acetic Acid (VIA) in cervical cancer screening in Padang primary health center. With r (0,248) and signification 0.090.Keywords: Visual Inspection with Acetic Acid (VIA), Midwife, Level Of Knowledge, Attitude